Maintenance of virulence markers in the UPM 93273 IBDV isolate after 48 passages in SPF embryonated chicken eggs - Hashim, Thuzar Than @ Hafiza; Ideris, Aini; Omar, Abdul Rahman (Universiti Putra Malaysia Press, 2004)
Infectious bursal disease virus (IBDV) is highly contagious and immunosuppressive in chickens. Virus neutralizing epitopes reside in the VP2 hypervariable region (hv) which harbor the most characteristic markers of virulence. The hv of UPM 93273 IBDV isolate and its various passages (wild type, P4, P15, P25, P31, P40, P48) were amplified by RT-PCR, cloned into pCR-TOPO cloning vector and sequenced. Sequence alignment and analysis of UPM 93273 isolate and other IBDV strains ranging from mild to very virulent strains were carried out using the Bio-Edit software. Most of the virulent markers were still maintained even after passage 48 in embryonated chicken eggs and this isolate is still very virulent and pathogenic. As a conclusion, further passages are needed to achieve a sufficient attenuation for UPM 93273 to be a potent IBD vaccine.